«It is necessary to bring sincere thanks to the donators who willingly responded to the call of the church to help in difficult times...»: report on activities of the Parish Council of Omsk Bogoroditze-Bratskaya Church for 1929 - A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
This archaeographic publication is devoted to study of history of Orthodoxy in Omsk at the late 1920s. The report on the activities of the Parish Council of Omsk Bogoroditze-Bratskaya Church for 1929 is being introduced into the scientific circulation. On the basis of published document, the conditions for existence of the largest Orthodox community of Bogoroditze-Bratskaya Church in Omsk are disclosed. It denotes a change in government policy from struggle with religion, which consisted in the transition from taxation turned out to be insufficiently effective pressure on the community, to political repression against its leaders. The work is addressed to researchers of the Soviet society, specialists in the history of the Russian Orthodox Church